Eco-Theology in the Catholic Perspective (A Study on Environmental Conservation Verses) at Santa Maria Cathedral Church, Palembang - Suryani; Nur Fitriyana; Nugroho; Zaki Faddad Syarif Zain (International Journal of Social Science and Religion (IJSSR), 2026)
This study aims to identify issues related to the understanding and implementation of eco-theological teachings based on Genesis 1:26–28 and Psalm 24:1 in the lives of the faithful at Santa Maria Cathedral Church, Palembang, and to position eco-theology as a theological foundation for ecological responsibility. The research employs a qualitative method through interviews with key informants and a literature review of journals and articles related to Catholic eco-theology. The main findings indicate that the congregation understands eco-theology as a faith-based calling manifested in waste management, greening initiatives, and participation in church ecological programs. This study contributes to the development of theology, religious environmental studies, and pastoral practices that promote ecological awareness. The novelty of this research lies in the integration of local empirical data with Catholic eco-theological literature, emphasizing that ecological care is a spiritual practice shaping the behavior of the faithful.